Parallelized Immunomagnetic Isolation of Basophils Directly from Whole Blood - Justin Myles; Nicolas Castaño; Sungu Kim; Zhenyun Zhu; Sindy K.Y. Tang (Advanced NanoBiomed Research, 2024)
Basophils are the rarest circulating white blood cells (WBCs), but they play important roles in allergic disorders and other diseases. To enhance diagnostic capabilities, it would be desirable to isolate and analyze basophils efficiently from small blood samples. In 100 μL of whole blood, there are typically ≈103 basophils, outnumbered by ≈105 WBCs and ≈108 red blood cells (RBCs). Basophils’ low abundance has therefore presented a significant challenge in their isolation from whole blood. Conventional in‐bulk basophil isolation methods require lengthy processing steps and cannot work with small volumes of blood. Herein, a parallelized integrated basophil isolation device (pi‐BID) is reported for the negative immunomagnetic selection of basophils directly from four samples of 100 μL of whole blood, in parallel, within 14 min including sample preparation time. The pi‐BID interfaces directly with standard sample tubes, and uses a single pressure source to drive the flow in parallel microfluidic channels. Compared with conventional in‐bulk basophil isolation, the pi‐BID is >3× faster, and has higher purity (≈93%) and similar recovery (≈67%). Compared with other microfluidic devices for the immunomagnetic isolation of WBC subtypes, the pi‐BID achieves 10× higher enrichment of target cells from whole blood, with no prior removal of RBCs necessary.